Językowo-kulturowy obraz mocy piekielnych w rosyjskiej i polskiej frazeologii i paremiologii - Różańska, Kinga (Acta Polono-Ruthenica, 2008)
The aim of this article is to present fragments of image of infernal powers and their relationships to other characters which were depicted in idiomatic expressions and proverbs of Russian and Polish language. The analysis of the material presented in this work shows identities and dissimilarities revealed in linguistic image of internal powers (devil, evil spirit, fiend, Satan): both features which are characteristic to infernal powers only and features characteristic to infernal powers and humanbeings. The article describes the relationships between man, priest and angel as well as appearanceand behavior of infernal powers. The line of thought reveals that, despite common religious roots and customs, linguistic image of infernal powers in Russian and Polish language is different.